Faktor Determinan Kelelahan Kerja Pada Guru SMP Negeri Di Kelurahan Baru Kota Makassar - Mauliana Putri AB; Ikhram Hardi S; Suharni A. Fachrin (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
High job demands on teachers can increase the risk of job burnout, which negatively impacts activities, the work environment, and productivity. Teachers are required to adapt to varying workloads, and addressing these demands is crucial for their well-being. This study aims to analyze the determinants of job burnout in public junior high school teachers in Baru Village, Makassar City, including age, nutritional status, length of service, workload, and job stress levels. This research emphasizes that workload and job stress are key factors teachers and administrators should focus on to foster well-being. The study used a quantitative, cross-sectional design. The study population was 70 teachers, with a sample of 64 respondents selected using a proportional random sampling technique. Data were analyzed using the chi-square test with a 95% confidence level (α = 0.05). The results showed a significant relationship between age (p < 0.001), workload (p < 0.001), and job stress levels (p < 0.001) with job burnout in teachers. Meanwhile, nutritional status (p = 0.576) and length of service (p = 0.869) did not show a significant relationship with job burnout. In conclusion, workload and job stress levels are significant factors contributing to teacher burnout. Schools should actively manage these factors to support teacher well-being and productivity.